Development of recent chronologies and evaluation of temporal variations in Pb fluxes and sources in lake sediment and peat cores in a remote, highly radiogenic environment, Cairngorm Mountains, Scottish Highlands. (1st May 2015) - Farmer, John G.; MacKenzie, Angus B.; Graham, Margaret C.; Macgregor, Kenneth; Kirika, Alexander
Abstract: The use of stable Pb isotope analyses in conjunction with recent ( 210 Pb and anthropogenic radionuclide) chronologies has become a well-established method for evaluating historical trends in depositional fluxes and sources of atmospherically deposited Pb using archival records in lake sediment or peat cores. Such studies rely upon (i) simple radioactive disequilibrium between unsupported 210 Pb and longer-lived members of the 238 U decay series and (ii) well-defined values for the isotopic composition of contaminant Pb and indigenous Pb in the study area. However, areas of high natural radioactivity can present challenging environments for such studies, with potential complications arising from more complex disequilibria in the 238 U decay series and the occurrence, at local or regional level, of anomalous, ill-defined stable isotope ratios due to the presence of elevated levels of radiogenic Pb. Results are presented here for a study of a sediment core from a freshwater lake, Loch Einich, in the high natural radioactivity area of the Cairngorm Mountains of Scotland. 238 U decay series disequilibria revealed recent diagenetic re-deposition of both U and 226 Ra, the latter resulting in a requirement to use a modified calculation to derive a 210 Pb chronology for the core. Confidence in the chronology was provided by good agreement with the independent 241 Am chronology, but the 137 Cs distribution was affected by significant post-depositional mobility in the organic-rich sediment. The systematics of variations in 230 Th, 232 Th and stable Pb isotope ratio distributions were used to establish the indigenous Pb characteristics of the sediment. The relatively high radiogenic content of the indigenous Pb resulted in complications in source apportionment, in particular during the 20th century, with multiple natural and anthropogenic sources precluding the use of a simple binary mixing model. Consequently, 206 Pb/ 207 Pb ratios in Scottish moss samples from an archive collection were used to provide the input term for atmospheric deposition in order to establish historical trends in indigenous and anthropogenic Pb fluxes. A test of the accuracy of the derived Pb fluxes was provided by analysis of a core from a nearby blanket peat deposit, Great Moss. Independent atmospheric and basal inputs gave a complex distribution of 210 Pb in the peat, but this did not affect calculation of a 210 Pb chronology. Once again, the 210 Pb chronology was supported by the 241 Am distribution. Temporal trends in anthropogenic Pb deposition derived for the Loch Einich sediment core were in generally good agreement with those for the Great Moss peat core, other peat cores and some other lake sediment cores from northern Scotland, providing confidence in the use of the archive moss data to characterise atmospheric deposition. However, sustained input of Pb to Loch Einich sediment at relatively high levels in the late 20th century, after the regional decline in atmospheric Pb deposition, suggested that catchment-derived Pb is now a significant component of the depositional flux for Loch Einich.